Sound souvenirs : audio technologies, memory and cultural practices - Bijsterveld, Karin, 1961-; Dijck, José van (Transformations in art and culture., 2009)
"In recent decades, the importance of sound for remembering the past and for creating a sense of belonging has been increasingly acknowledged. We keep "sound souvenirs" such as cassette tapes and long play albums in our attics because we want to be able to recreate the music and everyday sounds we once cherished. Artists and ordinary listeners deploy the newest digital audio technologies to recycle past sounds into present tunes. Sound and memory are inextricably intertwined, not just through the commercially exploited nostalgia on oldies radio stations, but through the exchange of valued songs by means of pristine recordings and cultural practices such as collecting, archiving and listing. This book explores several types of cultural practices involving the remembrance and restoration of past sounds. At the same time, it theorizes the cultural meaning of collecting, recycling, reciting, and remembering sound and music"--Publisher's description